Platelet aggregation and von Willebrand factor in patients with artherial hypertension combined with osteoarthritis - Viktoriya Rodionova; Olena Khmel (National Scientific Medical Center, 2017)
Objective: To investigate the platelet aggregation and level of von Willebrand factor in patients with hypertension and knee osteoarthritis. Methods: The study involved 102 people: 29 patients with hypertension stage II combined with osteoarthritis stage II - main group; 29 patients with hypertension stage II - frst group of comparison, 24 patients with osteoarthritis stage II - second group of comparison. The control group consisted of 20 almost healthy persons. Methods: ambulatory blood pressure monitoring, optical platelet aggregation test (inducers of platelet aggregation - adenosine diphosphate, collagen, thrombin, ristocetin (2 micromole)). Results: Von Willebrand factor was higher in patients with hypertension combined with osteoarthritis and in patients with isolated hypertension (182.6 [171.6 - 201.7] %, 184.8 [171.6 - 207.7] % respectively), compared to patients with osteoarthritis (167 [144.6 - 181.6] %) and the control group (163.4 [151.7 - 172.3] %) (p<0.05). The degree of platelet aggregation with adenosine diphosphate in patients with hypertension combined with osteoarthritis and in patients with hypertension had signifcant correlations with level of total cholesterol and daily index of systolic blood pressure (p <0.05)). Conclusion: Von Willebrand factor, degree platelet aggregation induced by adenosine diphosphate, collagen and thrombin were higher in patients with hypertension combined with osteoarthritis and in patients with hypertension compared to both the group of patients with osteoarthritis and control group (p <0.05). The degree of platelet aggregation with adenosine diphosphate was inﬂuenced by the level of total cholesterol and daily index of systolic blood pressure, the degree of platelet aggregation with collagen was inﬂuenced by daily index of systolic blood pressure and daily index of diastolic blood pressure (p<0.05).